Effectiveness of Emotion-Focused Therapy on Love Trauma Syndrome and Symptoms of Depression and Anxiety in Young Women with Experiences of Emotional Breakup - Ebrahimi, Fazeleh; Amini, Naser; Keykhosravani, Moloud (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: One of the most painful experiences in the collapse of romantic relationships is the experience of love trauma. The objective of the present study was to determine the effectiveness of emotion-focused therapy (EFT) on love trauma syndrome and symptoms of depression and anxiety in young women with experiences of emotional breakup. Methods and Materials: This study employed an applied quasi-experimental design with a pre-test, post-test, and follow-up with a control group. The statistical population of this study included all women aged 20-35 who visited counseling centers in Amol in 2022. The sample consisted of 40 women from the statistical population of Amol, who were selected through convenience sampling and randomly assigned to two groups: the emotion-focused therapy group (n=20) and the control group (n=20). Data were collected using the Ross Love Trauma Inventory (1999), Beck Anxiety Inventory (BAI), and Beck Depression Inventory (BDI) (1996). The sessions of emotion-focused therapy by Greenberg et al. (2008) were conducted in 12 weekly 90-minute sessions. Data were analyzed using repeated measures and SPSS-26 software. Findings: The results indicated that emotion-focused therapy was effective on anxiety (F = 18.410), depression (F = 41.531), and love trauma syndrome (F = 74.597) in young women with experiences of emotional breakup. Therefore, it can be concluded that emotion-focused therapy was effective on anxiety (F = 18.410), depression (F = 41.531), and love trauma syndrome (F = 74.597) in young women with experiences of emotional breakup. Conclusion: It can be concluded that emotion-focused therapy was effective on love trauma syndrome and symptoms of depression and anxiety in young women with experiences of emotional breakup.